1992
DOI: 10.1073/pnas.89.22.10993
|View full text |Cite
|
Sign up to set email alerts
|

Expression cloning of a reserpine-sensitive vesicular monoamine transporter.

Abstract: A cDNA for a rat vesicular monoamine transporter, desgatd MAT, was isolated by expression cloning in a mammalian cell line (CV-1). (1-4). The biogenic amine Na+-dependent transporters (reuptake transporters) located at the plasma membrane are responsible for transport of the released monoamines back into the cytoplasm, where they may be repackaged by the vesicular transporter into storage organelles or degraded by monoamine oxidases (5, 6).Several distinguishing features of the MAT are as follows: (i) broad s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
299
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 429 publications
(309 citation statements)
references
References 15 publications
(20 reference statements)
9
299
0
1
Order By: Relevance
“…VMAT2 is a neuronally expressed subtype of the vesicular monoamine transporter responsible for loading synaptic vesicles with the monoamine neurotransmitters serotonin, norepinephrine, dopamine, and histamine (Liu et al, 1992;Peter et al, 1994;Erickson et al, 1992Erickson et al, , 1996. Mice lacking both copies of the VMAT2 gene die during development, but heterozygotes survive and show reduced amphetamineconditioned reward, enhanced amphetamine and cocaineinduced locomotion, and enhanced MPTP toxicity (Takahashi et al, 1997;Wang et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…VMAT2 is a neuronally expressed subtype of the vesicular monoamine transporter responsible for loading synaptic vesicles with the monoamine neurotransmitters serotonin, norepinephrine, dopamine, and histamine (Liu et al, 1992;Peter et al, 1994;Erickson et al, 1992Erickson et al, , 1996. Mice lacking both copies of the VMAT2 gene die during development, but heterozygotes survive and show reduced amphetamineconditioned reward, enhanced amphetamine and cocaineinduced locomotion, and enhanced MPTP toxicity (Takahashi et al, 1997;Wang et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Once released from the cell, amines can be subject to reuptake by another set of transporters localised to the plasma membrane (Rothman and Orci, 1992;Calakos and Scheller, 1994). Two subtypes of vesicular monoamine transporters, VMAT1 and 2, have been characterised with structural similarities, but with differences in substrate specificity and tissue distribution (Erickson et al, 1992;Liu et al, 1992;Erickson and Eiden, 1993). In a recent study, we demonstrated the differential expression of VMAT1 and 2 in gut NE tumours, reflecting specific amine production and different cellular origin of these tumours.…”
mentioning
confidence: 83%
“…Probably as little as four transport proteins account for accumulation of transmitter in synaptic vesicles: the acetylcholine transporter (Koeningsberger and Parsons, 1980), a GABA/glycine transporter (Fyske and Fonnum, 1988;Hell et al, 1988;Kish et al, 1989), a glutamate carrier (Disbrow et al, 1982;Naito and Ueda, 1983;Maycox et al, 1988) and a non-specific monoamine carrier (see Njus et al, 1986;Erickson et al, 1992;Liu et al, 1992). Large, dense-cored vesicles may only contain the monoamine carrier and contain peptides that they have received while budding from the Golgi apparatus.…”
Section: The Availability Of Transmitters For Releasementioning
confidence: 99%